Glycerol conversion into a single cell oil by engineered Yarrowia lipolytica. Issue 3 (8th September 2016) - Gajdoš, Peter; Nicaud, Jean‐Marc; Čertík, Milan
Abstract : Oleaginous yeasts are considered as natural single cell oil producers. Engineering the lipid biosynthetic pathway has the potential to increase lipid accumulation by these yeasts. In Yarrowia lipolytica, three diacylglycerol acyltransferases encoded by LRO1, DGA1, and DGA2 genes are involved in lipid formation. Strain JMY3580 was constructed by overexpressing DGA2 gene in Q4 strain ( dga1 Δ dga2 Δ lro1 Δ are1 Δ). Reconstruction of triacylglycerol synthesis pathway led to significant improvement in lipid accumulation. Strain JMY3580 accumulated over 40% of lipids in biomass, while lipid accumulation in wild‐type strain was not able to exceed 20% when grown on a glycerol‐based medium with carbon to nitrogen ratio of 90. Higher lipid accumulation (over 50%) was achieved in fed‐batch grown cells when glycerol was added during cultivation. The best biomass yield was 18.5 g/L after 144 h with total fatty acid yield 9.9 g/L. Fatty acid composition was altered when Dga2p was the only diacylglycerol acyltransferase present in yeast cells, especially lower percentage of linoleic acid was present in lipids of JMY3580. Microbial oil prepared by conversion of glycerol by genetically engineered Y. lipolytica could be applied for various value‐added products based on single cell oils.